The effect of chatbot-based exercise interventions on physical activity, exercise habits, and sedentary behavior: A systematic review and meta-analysis of randomized controlled trials - Qian Wang; Wenxian Yang; Kai Xu; Lawrence T Lam (Digital Health, 2025)
Objectives Chatbots, transcending the limitations of space and time while reducing user resistance, offer a personalized and autonomous approach potentially enhancing digital health interventions. This systematic review aims to quantitatively evaluate the effectiveness of chatbot-based exercise interventions (EIs) in randomized controlled trials (RCTs), emphasizing physical activity (PA), exercise habits (EH), and sedentary behavior (SB). Methods A comprehensive search was carried out across Embase, Web of Science, PubMed, and Cochrane databases for studies published from January 2010 to October 2024. The characteristics of the included studies and the employed chatbots were analyzed. A meta-analysis was performed to synthesize the impact of chatbot-based EIs on PA, EH, and SB. We carried out subgroup analyses (SAs) for investigating potential modifying effects. Results This review includes 12 studies conducted between 2013 and 2024, encompassing 2446 participants and 240 parent-child dyads, with participant ages ranging from 8 to 71 years. The chatbot-based EIs significantly enhanced PA compared to control groups (SMD = 0.20, 95% CI = 0.04–0.37, p  = 0.02; I² = 51%, p  = 0.04). However, these interventions did not significantly impact EH (SMD = 0.29, 95% CI = −0.48–1.06, p  = 0.46) or reduce SB (SMD = 0.32, 95% CI = −0.54–1.19, p  = 0.46). Notably, SAs revealed a small but significant short-term increase in EH (SMD = 0.29, 95% CI = 0.08–0.50, p  = 0.006). Conclusion Chatbot-based EIs appear promising in improving PA, particularly moderate to vigorous PA (MVPA). Nonetheless, further RCTs with diverse chatbot designs, larger sample sizes, low-resource settings, objective measures of SB (e.g., accelerometers), and extended follow-ups are essential to corroborate these findings. Future research should also explore the adaptation of chatbots to various socioeconomic and cultural contexts and the integration of technologies like ChatGPT into EIs. Trial Registration: Meta-analysis PROSPERO: CRD42024609852